Multi-instrument study of a spread-F event at Arecibo linked to solar wind variations - Bostan, Salih Mehmed; Urbina, Julio, V; Mathews, John D.; Dinsmore, Ross L.; Robinson, Robert M. (Pergamon-Elsevier Science Ltd, 2023)
Using five diverse data sets, we demonstrate that apparently local ionospheric spread-F activity, observed with an HF radar and the Arecibo Observatory (AO) Incoherent Scatter Radars (ISR) under geomagnetically quiet conditions, is likely the local manifestation of a mesoscale or larger ionospheric response to relatively weak solar wind activity. The solar wind activity included a weak pressure pulse and Interplanetary Magnetic Field (IMF) realignment events. The mid-latitude spread-F activity was observed with a 4.42 MHz radar located near AO and the dual-beam 430 MHz AO ISRs. Additionally, the Coupling, Energetics and Dynamics of Atmospheric Regions (CEDAR) Madrigal Global Navigation Satellite System-Total Electron Content (GNSS-TEC), the NASA OMNI, and the SuperMAG datasets were used to establish the (mesoscale/global) wide-context of the local, deep-context radar results. While the ISR event appears to be classicallocal spread-F, often attributed to Perkins-like plasma instabilities, the HF radar reveals large ionospheric structures coincident with the ISR event. However, that the apparently AO-local event was part of a very dynamic mesoscale event that lasted for over ten hours, is shown via independent AO-sector and AO-conjugate sector keograms constructed using detrended vertical TEC (delta-vTEC) data. The keograms reveal a prominent F-region feature that appears to propagate from west-to-east and then back to the west passing over AO twice. The ISR manifestation of this mesoscale event is indistinguishable from decades of similar ISR results which were assumed to be strictly local. The strong non-local (mesoscale) properties revealed by the delta-vTEC keograms suggest a possible space weather influence. Study of the relevant NASA OMNI solar wind and superMAG magnetometer data points to modest solar wind features including IMF realignment that may have electrodynamically launched, with little time delay, the observed mesoscale ionospheric events. Given the apparent rapid ionospheric response to the solar wind features, we suggest that limited latitudinal scale, prompt penetration electric fields (PPEF), associated with highly-localized partial ring current activity, be considered in the system-of-systems context of our observations. In any case, the need to examine magnetospheric/ionospheric electrodynamics across a wide range of instruments and data sets is demonstrated.
Keywords: Mid-latitude spread-F; Ionospheric irregularities; Solar wind pressure pulses; GNSS delta-vTEC keograms